Identification and monitoring of metabolite markers of dry bean consumption in parallel human and mouse studies. Issue 4 (23rd February 2015) - Perera, Thushanthi; Young, Matthew R.; Zhang, Zhiying; Murphy, Gwen; Colburn, Nancy H.; Lanza, Elaine; Hartman, Terryl J.; Cross, Amanda J.; Bobe, Gerd
<x xml:space="preserve">Abstract</x> Scope Aim of the study was to identify and monitor metabolite markers of dry bean consumption in parallel human and mouse studies that each had shown chemopreventive effects of dry bean consumption on colorectal neoplasia risk. Methods and results Using LC/mass spectroscopy ± ESI and GC/mass spectroscopy, serum metabolites of dry beans were measured in 46 men before and after a 4‐week dry bean enriched diet (250 g/day) and 12 mice that received a standardized diet containing either 0 or 10% navy bean ethanol extract for 6 weeks; we also investigated fecal metabolites in the mice. The serum metabolites identified in these controlled feeding studies were then investigated in 212 polyp‐free participants from the Polyp Prevention Trial who self‐reported either increased (≥+31 g/day from baseline), high dry bean intake of ≥42 g/day in year 3 or low, unchanged dry bean consumption of <8 g/day; serum was analyzed from baseline and year 3. Serum pipecolic acid and S‐methyl cysteine were elevated after dry bean consumption in human and mouse studies and reflected dry bean consumption in the Polyp Prevention Trial. Conclusion Serum levels of pipecolic acid and S‐methyl cysteine are useful biomarkers of dry bean consumption.